2022
DOI: 10.3390/toxins14030188
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Fatty Acids and Their Derivatives as Antifungal Agents: A Review

Abstract: Fungal contamination presents several problems: in humans, health issues arise from infections with opportunistic filamentous fungi and yeast, while in food, fungi cause spoilage and, in particular, in the case of mycotoxigenic fungi, can cause serious health issues. Several types of fatty acids and their derivatives, oxylipins, have been found to have inhibitory effect towards fungal growth and the production of mycotoxins. The use of fatty acids as antifungals could fulfil consumer’s requests of more natural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 118 publications
1
26
0
Order By: Relevance
“…Moreover, much research has demonstrated that most hydrocarbon-degrading bacteria can readily use alkanes in the C14-C20 range as an energy source [24]. Several reports have also described a combination of b-hydroxy fatty acids of dodecanoic, tetradecanoic, pentadecanoic, hexadecenoic, octadecanoic, (9)-octadecenoic and (9,12)-octadecadienoic in the lipopeptide biosurfactant [60], which was confirmed with our study. Saturated fatty acids have been reported to exert inhibitory activity towards some fungal species; hydrophobic groups of SFA seem to play a role in the antimicrobial activity.…”
Section: The Effect Of Treatments On the Morphology Of Mycelium Of Fu...supporting
confidence: 89%
“…Moreover, much research has demonstrated that most hydrocarbon-degrading bacteria can readily use alkanes in the C14-C20 range as an energy source [24]. Several reports have also described a combination of b-hydroxy fatty acids of dodecanoic, tetradecanoic, pentadecanoic, hexadecenoic, octadecanoic, (9)-octadecenoic and (9,12)-octadecadienoic in the lipopeptide biosurfactant [60], which was confirmed with our study. Saturated fatty acids have been reported to exert inhibitory activity towards some fungal species; hydrophobic groups of SFA seem to play a role in the antimicrobial activity.…”
Section: The Effect Of Treatments On the Morphology Of Mycelium Of Fu...supporting
confidence: 89%
“…Benzyl Alcohol has been proven to induce attack on bacterial membranes and protein denaturation, following an increase of reactive oxygen species levels [ 42 ]. Linoleic acid as fatty acid was involved in affecting membrane permeability (pore formation and membrane destabilization), reducing hydrophobicity but being able to interfere with microbial metabolism or signaling [ 43 ]. Palmitic acid was observed to enhance hyphal growth for C. tropicalis through upregulation of hyphal wall protein (HWP1) and enhanced filamentous growth (EFG1) genes [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among these latter, (12Z,15Z)-9,10-epoxyoctadeca-12,15-dienoate and (9Z,12Z)-15,16-dihydroxyoctadeca-9,12-dienoate, which are involved in the production of hydroxy fatty acids from α-linolenic acid, were oppositely affected by the UV-B exposure, being increased or decreased, respectively. Since some hydroxylated fatty acids act as antifungal agents [ 27 ], the influence of UV-B radiation on this pathway may lead to changes in plant–pathogen interactions.…”
Section: Resultsmentioning
confidence: 99%